Genetic polymorphisms, vitamin D binding protein and vitamin D deficiency in COVID-19. Issue 5 (6th May 2021) - Faniyi, Aduragbemi A.; Lugg, Sebastian T.; Faustini, Sian E.; Webster, Craig; Duffy, Joanne E.; Hewison, Martin; Shields, Adrian; Nightingale, Peter; Richter, Alex G.; Thickett, David R.
We thank M.M. Speeckaert and co-workers for their interest in our paper about vitamin D status and seroconversion for coronavirus disease 2019 (COVID-19) in UK healthcare workers [1]. We agree with the authors that vitamin D binding protein (DBP) is important in determining serum 25(OH)D3 levels. The majority of vitamin D in the circulation is bound to DBP, also known as gc-globulin, which has actin-binding and immunomodulatory functions independent of vitamin D carriage [2]. DBP levels may be particularly relevant to determining 25(OH)D3 levels in severely ill COVID-19 patients with acute respiratory distress syndrome (ARDS), as we have previously demonstrated that DBP is a negative acute phase protein with levels dropping by about a third in patients with ARDS [3]. This tends to lower circulating total vitamin D but releases free 25(OH)D that can be taken up by cells of the immune system and epithelial cells. The consequences of changes in serum 25(OH)D during illness are, therefore, complex and difficult to interpret [4]. Genome-wide association analyses have shown that single nucleotide polymorphisms (SNPs) in the gene for DBP ( GC ) are important contributors to the genetic component of circulating 25D concentrations, but this is still a relatively small proportion of overall serum 25D levels, and it is unclear how these SNPs impact DBP/25D homeostasis in the setting of disease. This work outlines the potential importance of vitamin D binding protein and vitamin D in immune function and COVID-19 infection https://bit.ly/3byTaO5